Implementasi Konsep Zakat dalam Al- Qur’an Sebagai Upaya Mengentaskan Kemiski nan Di Di Indonesia - Junaidi Safitri (Mukaddimah: Jurnal Studi Islam, 2018)
This study aims to explain the concrete steps in an effort to convey their zakat potential in Indonesia is predominantly Muslim, in this case the charity is directed how to create the harmony between the rich and the poor through the analysis of the zakat institutions that exist, with the noble purpose, namely to reduce poverty , So the zakat teachings in the Koran, can be realized as a path that creates the harmony of human life, both physically and mentally. This study uses qualitative descriptive method by researching library materials (library research). The results of these empirically shows that the First, Zakat in the Qur’an has a positive correlation to economic growth, due to its nature as a distribution of income that can improve the function of consumption and production are balanced. Second, the potential of zakat in Indonesia macro can be optimized through the government’s role as regulator and supervisor in the management of zakat in Indonesia. And Third, the concept of zakat as described above have an opportunity as a source of state revenue that is allocated specifically for the alleviation of poverty, meaning that the source of state revenue derived from zakat should be given to the mustahiq both consumptive and productive.